السّلالم الحجاجيّة في السّور المسبّحات من القرآن الكريم - باي, راضية; سويد, فتيحة; واغد, وردة (جامعة الوادي - University of Eloued, 2023)
يُعدّ السّلم الحجاجي من أهمّ السّمات الحجاجيّة التي تعتمد على التّراتبيّة في توجيه الحجّج. وأهميتها تتجلّى في ترتيب تلك الحجّج من حيث القّوة والضّعف بشكّل سلّمي ؛ للتّأثير في المتلقي وعليه فالسّلالم الحجاجيّة مؤشّر واضح على مرونة اللغة وقوّة المنطق الطّبيعي ,الذي يستطيع المتكلّم من خلاله إنجاز الاقتناع من دون اللّجوء إلى أساليب المنطق الرّياضي البرهاني . والخطابُ القرآني معجزٌ في ألفاظه وتراتبيّة حُججِه من الأضعف إلى الأقوى, أو العكس ؛ قصد استمالة المخاطب وإذعانه بأسلوب خال من العنف والإكراه . وعلى هذا الأساس جاءت فكرة بحثنا هذا قصد تتبّع السّلميّة الحجاجيّة في السّور المسبحات من القرآن الكريم ، الذي غـذّى ميولنا الشّديدة للبحث فيه ، رغبة منّا في الاستفادة من هذا العلم الواسع ، وفهم نظريّة السّلالم الحجاجيّة واستثمارها في تحليل الخطابات القرآنيّة . توصّلنا من خلال هذه المدوّنة الخصبة التي تنضح بالمعلومات إلى : وجود تعالق واضح بين موضوعات السّور المسبّحات, والذي انسجم مع استهلالها بالتّسبيح ؛ فموضوعاتُ كلِّ هذه السَّورِ تقتضي التَّسبيح. تحقّق تراتبية حجاجيّة عجيبة في معانيها تمثّلت في: 1- تراتبيّة السّور المسبّحات في المصحف حسب الترتيب الاشتقاقي للغة ،وتراتبيتُها حسب مواطن التسبيح فيها , و تراتبيتها حسب موضوعاتها. 2- أنّ سلّميّة الحوارات الواردةِ في السّور مرتّبةٌ حسب مواضيعها وأغراضها. 3- مجيء تراتبيّة أسماء اللّه الحسنى في السّور كان حسب المخاطَب والسّياق المقامي. 4- الكشف عن تراتبيّة عجيبة سواءً في: المدارج المعجميّة أو الصّيغ الصّرفيّة أو التراكيب النّحويّة أو التّقسيم البلاغي. 5- سورة الإسراء هي نواة السّور المسبّحات، حيث علت قمّة السّلم في أغلب السّلالم المنجزة ، وهي سورة لا تضاهيها سورةٌ أخرى في احتوائها على صيغ التّسبيح ؛ ولعل في ذلك إشارة إلى حقيقة نقل الرّسول  إلى عالم التّسبيح . Synopsis : The pilgrim ladder is one of the most important features of the pilgrimage, which relies on hierarchy in directing arguments. Therefore, the pilgrim stairs are a clear indicator of the flexibility of the language and the strength of natural logic ,through which the speaker can achieve conviction without resorting to the methods of mathematical-demonstrative logic . The Quranic speech is miraculous in its pronunciation and the hierarchy of its arguments from the weakest to the strongest, or vice versa; in order to coax the interlocutor and obey him in a manner free from violence and coercion . On this basis, the idea of our research came in order to trace the peaceful Hajj pilgrimage in the surahs of the rosaries from the Holy Quran, which fueled our strong tendencies to research it, our desire to benefit from this broad Science, understand the theory of Hajj stairs and invest it in the analysis of Quranic discourses . Through this lush and informative blog we have come to : There is a clear correlation between the topics of the surahs of the rosaries, which is consistent with their beginning with praise; the topics of all these surahs require praise. A strange Pilgrim hierarchy is realized in its meanings, represented by: 1-the sequence of the surahs of the rosaries in the Quran according to the etymological order of the language , their sequence according to the subjects of praise in it, and their sequence according to their topics. 2-the peaceful dialogues contained in the Surah are arranged according to their themes and purposes. 3-the coming of the hierarchy of the names of Allah in the Surah was according to the addressee and the local context. 4-revealing a strange hierarchy whether in: lexical rungs, morphological formulas, grammatical structures or rhetorical division. 5-Surah Al-Isra is the nucleus of the Surah Al-rosaries, where the top of the ladder is at the top of most of the completed stairs, and it is a Surah that is incomparable with other surahs in containing the formulas of praise; perhaps this is a reference to the fact of transferring the messenger to the world of praise .
لسانيات عامة
Keywords: الحجاج ، السلم ، السلميّة التراتبيّة ، سلم تنازليّ ، سلم تصاعدي; pilgrims, ladder, hierarchical ladder, descending ladder, ascending ladder